DETERMINAN PERTUMBUHAN EKONOMI KABUPATEN/KOTA DI JAWA TIMUR TAHUN 2019-2021 - Fajrul Ihsan; Marlina Ekawaty (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Economic growth is an illustration of economic development in an area, therefore the government always strives to ensure that economic growth continues to increase from year to year which will in turn improve people's welfare. This research aims to determine the influence of labor (X1), human development index (X2), government expenditure (X3), exports (X4) and the Covid-19 pandemic (DV) on economic growth (Y) in 38 districts and cities in Java East in 2019-2021. This research uses quantitative methods. Data processing uses the Eviews 10 application (2023). The results of this research can be concluded that labor (X1) has a positive and significant effect on economic growth (Y), the human development index (X2) has a positive and significant effect on economic growth (Y), government spending (X3) has no significant effect on economic growth (Y), exports (X4) has a positive and significant effect on economic growth (Y) and the covid-19 pandemic (DV) has a negative and significant effect on economic growth (Y).